Hubungan Antara Dukungan Sosial Orangtua dan Self Efficacy Dengan Kecemasan Dalam Menghadapi Dunia Kerja Pada Mahasiswa Semester Akhir Fakultas Psikologi Universitas Persada Indonesia YAI - Adi Muhammad Kasyfillah; Tanti Susilarini (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
This study aims to determine the relationship between parental social support and self-efficacy with anxiety indealing with the world of work in final semester students of the psychology faculty of Universitas Persada IndonesiaYAI. The sampling technique used was convenience sampling with a population of 182 students and a researchsample of 107 students. The data collection technique uses three scales, namely the anxiety scale in dealing with theworld of work, parental social support, and self-efficacy. The results of the first bivariate correlation analysisbetween parental social support and anxiety in dealing with the world of work obtained a correlation coefficient (r)of -0.344 with p = 0.000 <0.05. So Ha1 which reads "There is a relationship between parental social support andanxiety in dealing with the world of work in final semester students of the psychology faculty of Universitas PersadaIndonesia YAI", is accepted. The results of the second bivariate correlation between self-efficacy and anxiety indealing with the world of work obtained a correlation (r) of -0.689 with p = 0.000 <0.05. So Ha2 which reads "Thereis a relationship between self-efficacy and anxiety in dealing with the world of work in final semester students of thepsychology faculty of Universitas Persada Indonesia YAI" is accepted. The results of data analysis multivariatecorrelation between parental social support and self-efficacy with anxiety in dealing with the world of work obtained(R) of 0.718 with p = 0.000 <0.05. So Ha3 which reads "There is a relationship between parental social supportand self-efficacy with anxiety in dealing with the world of work in final semester students of the psychology facultyof Universitas Persada Indonesia YAI" is accepted